Proteomic Profiling Reveals Mitochondrial Dysregulation in Rapidly Progressive Alzheimer’s: Role of DLDH in Amyloid Beta Aggregation - Saima Zafar; Aneeqa Noor; Neelam Younas; Mohsin Shafiq; Kathrin Dittmar; Oleksandr Yagensky; Matthias Schmitz; Isidre Ferrer; Peter Hermann; Inga Zerr (Molecular Neurobiology, 2026)
Alzheimer’s disease (AD) is presented as multiple clinical variants depending upon the rate of progression and familial background; however, the exact molecular mechanisms associated with these subtypes and their treatments are yet to be understood. The current study is based on a global proteome analysis of brain samples from patients ( n = 38) with rapidly progressive AD (rpAD—survival time < 3 years), sporadic AD (spAD—survival time of 8–10 years), and healthy controls. Proteome analysis revealed a differential regulation of 79 proteins and highlighted the dysregulation of mitochondrial machinery and glucose metabolism in rpAD. Dihydrolipoamide dehydrogenase (DLDH), a mitochondrial oxidoreductase, showed a significant reduction and delocalization in rpAD. In vitro analysis revealed a potential role of DLDH in the aggregation of amyloid beta. Rapid progression in AD may be influenced by the energy homeostasis and redox dysfunction linked with the DLDH.

The Role of Tau Proteoforms in Health and Disease - Zuha Waheed; Jawaria Choudhary; Faria Hasan Jatala; Fatimah; Aneeqa Noor; Inga Zerr; Saima Zafar (Molecular Neurobiology, 2023)

Role of different recombinant PrP substrates in the diagnostic accuracy of the CSF RT-QuIC assay in Creutzfeldt-Jakob disease - Susana Margarida Da Silva Correia; Matthias Schmitz; Andre Fischer; Peter Hermann; Inga Zerr (Cell and Tissue Research, 2023)
The development of the real-time quaking-induced conversion (RT-QuIC), an in vitro protein misfolding amplification assay, was an innovation in the scientific field of protein misfolding diseases. In prion diseases, these types of assays imitate the pathological conversion of the cellular prion protein (PrP C ) into a protease-resistant and/or amyloid form of PrP, called PrP resistant (PrP Res ). The RT-QuIC is an automatic assay system based on real-time measuring of thioflavin-T (Th-T) incorporation into amyloid fibrils using shaking for disaggregation. It has already been applied in diagnostics, drug pre-screening, and to distinguish between different prion strains. The seeded conversion efficiency and the diagnostic accuracy of the RT-QuIC assay strongly depend on the kind of recombinant PrP (rec PrP) substrate. The DNA sequences of different substrates may originate from different species, such as human, bank vole, and hamster, or from a combination of two species, e.g., hamster-sheep chimera. In routine use, either full-length (FL) or truncated substrates are applied which can accelerate the conversion reaction, e.g., to a more sensitive version of RT-QuIC assay. In the present review, we provide an overview on the different types of PrP substrates (FL and truncated forms), recapitulate the production and purification process of different rec PrP substrates, and discuss the diagnostic value of CSF RT-QuIC in human prion disease diagnostics.

Synthesis, structural characterization and study of antioxidant and anti-PrPSc properties of flavonoids and their rhenium(I)–tricarbonyl complexes - Pigi Glykofridi; Vassiliki-Eleni Tziouri; Konstantinos Xanthopoulos; Maria-Eirini Vlachou; Susana Correia; Anna-Lisa Fischer; Katrin Thüne; Antonios Hatzidimitriou; Inga Zerr; Matthias Schmitz; Theodoros Sklaviadis; Dimitra Hadjipavlou-Litina; et al. (JBIC Journal of Biological Inorganic Chemistry, 2023)
This study aims at the synthesis and initial biological evaluation of novel rhenium–tricarbonyl complexes of 3,3′,4′,5,7-pentahydroxyflavone (quercetin), 3,7,4΄-trihydroxyflavone (resokaempferol), 5,7-dihydroxyflavone (chrysin) and 4΄,5,7-trihydroxyflavonone (naringenin) as neuroprotective and anti-PrP agents. Resokaempferol was synthesized from 2,2΄,4-trihydroxychalcone by H 2 O 2 /NaOH. The rhenium–tricarbonyl complexes of the type fac -[Re(CO) 3 (Fl)(sol)] were synthesized by reacting the precursor fac -[Re(CO) 3 (sol) 3 ] + with an equimolar amount of the flavonoids (Fl) quercetin, resokaempferol, chrysin and naringenin and the solvent (sol) was methanol or water. The respective Re–flavonoid complexes were purified by semi-preparative HPLC and characterized by spectroscopic methods. Furthermore, the structure of Re–chrysin was elucidated by X-ray crystallography. Initial screening of the neuroprotective properties of these compounds included the in vitro assessment of the antioxidant properties by the DPPH assay as well as the anti-lipid peroxidation of linoleic acid in the presence of AAPH and their ability to inhibit soybean lipoxygenase. From the above studies, it was concluded that the complexes’ properties are mainly correlated with the structural characteristics and the presence of the flavonoids. The flavonoids and their respective Re-complexes were also tested in vitro for their ability to inhibit the formation and aggregation of the amyloid-like abnormal prion protein, PrP Sc , by employing the real-time quaking-induced conversion assay with recombinant PrP seeded with cerebrospinal fluid from patients with Creutzfeldt–Jakob disease. All the compounds blocked de novo abnormal PrP formation and aggregation. Graphical abstract

Validation of Plasma and CSF Neurofilament Light Chain as an Early Marker for Sporadic Creutzfeldt-Jakob Disease - Matthias Schmitz; Sezgi Canaslan; Juan Carlos Espinosa; Natalia Fernández-Borges; Anna Villar-Piqué; Franc Llorens; Daniela Varges; Fabian Maass; Juan Maria Torres; Peter Hermann; Inga Zerr (Molecular Neurobiology, 2022)

Molecular Profiles of Amyloid-β Proteoforms in Typical and Rapidly Progressive Alzheimer’s Disease - Aneeqa Noor; Saima Zafar; Mohsin Shafiq; Neelam Younas; Anna Siegert; Florian A. Mann; Sebastian Kruss; Matthias Schmitz; Hassan Dihazi; Isidre Ferrer; Inga Zerr (Molecular Neurobiology, 2022)
The molecular determinants of atypical clinical variants of Alzheimer’s disease, including the recently discovered rapidly progressive Alzheimer’s disease (rpAD), are unknown to date. Fibrilization of the amyloid-β (Aβ) peptide is the most frequently studied candidate in this context. The Aβ peptide can exist as multiple proteoforms that vary in their post-translational processing, amyloidogenesis, and toxicity. The current study was designed to identify these variations in Alzheimer’s disease patients exhibiting classical (sAD) and rapid progression, with the primary aim of establishing if these variants may constitute strains that underlie the phenotypic variability of Alzheimer’s disease. We employed two-dimensional polyacrylamide gel electrophoresis and MALDI-ToF mass spectrometry to validate and identify the Aβ proteoforms extracted from targeted brain tissues. The biophysical analysis was conducted using RT-QuIC assay, confocal microscopy, and atomic force microscopy. Interactome analysis was performed by co-immunoprecipitation. We present a signature of 33 distinct pathophysiological proteoforms, including the commonly targeted Aβ 40 , Aβ 42 , Aβ 4-42 , Aβ 11-42 , and provide insight into their synthesis and quantities. Furthermore, we have validated the presence of highly hydrophobic Aβ seeds in rpAD brains that seeded reactions at a slower pace in comparison to typical Alzheimer’s disease. In vitro and in vivo analyses also verified variations in the molecular pathways modulated by brain-derived Aβ. These variations in the presence, synthesis, folding, and interactions of Aβ among sAD and rpAD brains constitute important points of intervention. Further validation of reported targets and mechanisms will aid in the diagnosis of and therapy for Alzheimer’s disease.

Validation of Poly(Propylene Imine) Glycodendrimers Towards Their Anti-prion Conversion Efficiency - Matthias Schmitz; Niccolo Candelise; Eirini Kanata; Franc Llorens; Katrin Thüne; Anna Villar-Piqué; Susana Margarida da Silva Correia; Dimitra Dafou; Theodoros Sklaviadis; Dietmar Appelhans; Inga Zerr (Molecular Neurobiology, 2020)

Cadmium induces GAPDH- and- MDH mediated delayed cell aging and dysfunction in Candida tropicalis 3Aer - Zaman Khan; Muhammad Atif Nisar; Saima Muzammil; Saima Zafar; Inga Zerr; Abdul Rehman (Environmental Monitoring and Assessment, 2019)

Cerebrospinal Fluid Total and Phosphorylated α-Synuclein in Patients with Creutzfeldt–Jakob Disease and Synucleinopathy - Matthias Schmitz; Anna Villar-Piqué; Franc Llorens; Karin Gmitterová; Peter Hermann; Daniela Varges; Saima Zafar; Paul Lingor; Hugo Vanderstichele; Leentje Demeyer; Erik Stoops; John Q Trojanowski; et al. (Molecular Neurobiology, 2019)

Cerebrospinal Fluid Total Prion Protein in the Spectrum of Prion Diseases - Anna Villar-Piqué; Matthias Schmitz; Ingolf Lachmann; André Karch; Olga Calero; Christiane Stehmann; Shannon Sarros; Anna Ladogana; Anna Poleggi; Isabel Santana; Isidre Ferrer; Eva Mitrova; et al. (Molecular Neurobiology, 2019)

Cerebrospinal Fluid Prion Disease Biomarkers in Pre-clinical and Clinical Naturally Occurring Scrapie - Franc Llorens; Tomás Barrio; Ângela Correia; Anna Villar-Piqué; Katrin Thüne; Peter Lange; Juan José Badiola; Matthias Schmitz; Ingolf Lachmann; Rosa Bolea; Inga Zerr (Molecular Neurobiology, 2018)

Molecular and Clinical Aspects of Protein Aggregation Assays in Neurodegenerative Diseases - Anna Villar-Piqué; Matthias Schmitz; Niccolò Candelise; Salvador Ventura; Franc Llorens; Inga Zerr (Molecular Neurobiology, 2018)

Validation of α-Synuclein as a CSF Biomarker for Sporadic Creutzfeldt-Jakob Disease - Franc Llorens; Niels Kruse; André Karch; Matthias Schmitz; Saima Zafar; Nadine Gotzmann; Ting Sun; Silja Köchy; Tobias Knipper; Maria Cramm; Ewa Golanska; Beata Sikorska; et al. (Molecular Neurobiology, 2018)

Molecular Alterations in the Cerebellum of Sporadic Creutzfeldt–Jakob Disease Subtypes with DJ-1 as a Key Regulator of Oxidative Stress - Waqas Tahir; Saima Zafar; Franc Llorens; Amandeep Singh Arora; Katrin Thüne; Matthias Schmitz; Nadine Gotzmann; Niels Kruse; Brit Mollenhauer; Juan Maria Torres; Olivier Andréoletti; Isidre Ferrer; et al. (Molecular Neurobiology, 2018)

Reelin Expression in Creutzfeldt-Jakob Disease and Experimental Models of Transmissible Spongiform Encephalopathies - Agata Mata; Laura Urrea; Silvia Vilches; Franc Llorens; Katrin Thüne; Juan-Carlos Espinosa; Olivier Andréoletti; Alejandro M. Sevillano; Juan María Torres; Jesús Rodríguez Requena; Inga Zerr; Isidro Ferrer; et al. (Molecular Neurobiology, 2017)

MicroRNA Expression in the Locus Coeruleus, Entorhinal Cortex, and Hippocampus at Early and Middle Stages of Braak Neurofibrillary Tangle Pathology - Franc Llorens; Katrin Thüne; Pol Andrés-Benito; Waqas Tahir; Belén Ansoleaga; Karina Hernández-Ortega; Eulàlia Martí; Inga Zerr; Isidro Ferrer (Journal of Molecular Neuroscience, 2017)

Hereditary Human Prion Diseases: an Update - Matthias Schmitz; Kathrin Dittmar; Franc Llorens; Ellen Gelpi; Isidre Ferrer; Walter J. Schulz-Schaeffer; Inga Zerr (Molecular Neurobiology, 2017)

Cytoskeleton-Associated Risk Modifiers Involved in Early and Rapid Progression of Sporadic Creutzfeldt-Jakob Disease - Saima Zafar; Neelam Younas; Nadeem Sheikh; Waqas Tahir; Mohsin Shafiq; Matthias Schmitz; Isidre Ferrer; Olivier Andréoletti; Inga Zerr (Molecular Neurobiology, 2017)

Effect of Metformin on Adult Hippocampal Neurogenesis: Comparison with Donepezil and Links to Cognition - Sara Ahmed; Zahra Mahmood; Aneela Javed; Shoaib Naiyer Hashmi; Inga Zerr; Saima Zafar; Saadia Zahid (Journal of Molecular Neuroscience, 2017)

Strain-Specific Altered Regulatory Response of Rab7a and Tau in Creutzfeldt-Jakob Disease and Alzheimer’s Disease - Saima Zafar; Neelam Younas; Susana Correia; Mohsin Shafiq; Waqas Tahir; Matthias Schmitz; Isidre Ferrer; Olivier Andréoletti; Inga Zerr (Molecular Neurobiology, 2017)

Validation of 14-3-3 Protein as a Marker in Sporadic Creutzfeldt-Jakob Disease Diagnostic - Matthias Schmitz; Elisabeth Ebert; Katharina Stoeck; André Karch; Steven Collins; Miguel Calero; Theodor Sklaviadis; Jean-Louis Laplanche; Ewa Golanska; Ines Baldeiras; Katsuya Satoh; Raquel Sanchez-Valle; et al. (Molecular Neurobiology, 2016)

Stability and Reproducibility Underscore Utility of RT-QuIC for Diagnosis of Creutzfeldt-Jakob Disease - Maria Cramm; Matthias Schmitz; André Karch; Eva Mitrova; Franziska Kuhn; Bjoern Schroeder; Alex Raeber; Daniela Varges; Yong-Sun Kim; Katsuya Satoh; Steven Collins; Inga Zerr (Molecular Neurobiology, 2016)
Real-time quaking-induced conversion (RT-QuIC) allows the amplification of miniscule amounts of scrapie prion protein (PrP Sc ). Recent studies applied the RT-QuIC methodology to cerebrospinal fluid (CSF) for diagnosing human prion diseases. However, to date, there has not been a formal multi-centre assessment of the reproducibility, validity and stability of RT-QuIC in this context, an indispensable step for establishment as a diagnostic test in clinical practice. In the present study, we analysed CSF from 110 prion disease patients and 400 control patients using the RT-QuIC method under various conditions. In addition, “blinded” ring trials between different participating sites were performed to estimate reproducibility. Using the previously established cut-off of 10,000 relative fluorescence units (rfu), we obtained a sensitivity of 85 % and a specificity of 99 %. The multi-centre inter-laboratory reproducibility of RT-QuIC revealed a Fleiss’ kappa value of 0.83 (95 % CI: 0.40–1.00) indicating an almost perfect agreement. Moreover, we investigated the impact of short-term CSF storage at different temperatures, long-term storage, repeated freezing and thawing cycles and the contamination of CSF with blood on the RT-QuIC seeding response. Our data indicated that the PrP Sc seed in CSF is stable to any type of storage condition but sensitive to contaminations with blood (>1250 erythrocytes/μL), which results in a false negative RT-QuIC response. Fresh blood-contaminated samples (3 days) can be rescued by removal of erythrocytes. The present study underlines the reproducibility and high stability of RT-QuIC across various CSF storage conditions with a remarkable sensitivity and specificity, suggesting RT-QuIC as an innovative and robust diagnostic method.

Creutzfeldt-Jakob Disease Subtype-Specific Regional and Temporal Regulation of ADP Ribosylation Factor-1-Dependent Rho/MLC Pathway at Pre-Clinical Stage - Saima Zafar; Matthias Schmitz; Neelam Younus; Waqas Tahir; Mohsin Shafiq; Franc Llorens; Isidre Ferrer; Olivier Andéoletti; Inga Zerr (Journal of Molecular Neuroscience, 2015)

Characteristic CSF Prion Seeding Efficiency in Humans with Prion Diseases - Maria Cramm; Matthias Schmitz; André Karch; Saima Zafar; Daniela Varges; Eva Mitrova; Bjoern Schroeder; Alex Raeber; Franziska Kuhn; Inga Zerr (Molecular Neurobiology, 2015)

Loss of Prion Protein Leads to Age-Dependent Behavioral Abnormalities and Changes in Cytoskeletal Protein Expression - Matthias Schmitz; Catharina Greis; Philipp Ottis; Christopher J. Silva; Walter J. Schulz-Schaeffer; Arne Wrede; Katharina Koppe; Bruce Onisko; Jesús R. Requena; Nambirajan Govindarajan; Carsten Korth; Andre Fischer; et al. (Molecular Neurobiology, 2014)

Anchorless 23–230 PrPC Interactomics for Elucidation of PrPC Protective Role - Saima Zafar; Abdul R. Asif; Sanja Ramljak; Waqas Tahir; Matthias Schmitz; Inga Zerr (Molecular Neurobiology, 2014)

Oligodendroglial Process Formation is Differentially Affected by Modulating the Intra- and Extracellular Cholesterol Content - Matthias Schmitz; Sandra C. Signore; Inga Zerr; Hans H. Althaus (Journal of Molecular Neuroscience, 2013)

ApoE Distribution and Family History in Genetic Prion Diseases in Germany - Anna Krasnianski; Nicolas von Ahsen; Uta Heinemann; Bettina Meissner; Hans A. Kretzschmar; Victor W. Armstrong; Inga Zerr (Journal of Molecular Neuroscience, 2008)

Genetic prion disease: the EUROCJD experience - Gábor G. Kovács; Maria Puopolo; Anna Ladogana; Maurizio Pocchiari; Herbert Budka; Cornelia van Duijn; Steven J. Collins; Alison Boyd; Antonio Giulivi; Mike Coulthart; Nicole Delasnerie-Laupretre; Jean Philippe Brandel; et al. (Human Genetics, 2005)

Polymorphisms within the prion-like protein gene (Prnd) and their implications in human prion diseases, Alzheimer's disease and other neurological disorders - Björn Schröder; Bettina Franz; Petra Hempfling; Martin Selbert; Thomas Jürgens; Hans A. Kretzschmar; Monika Bodemer; Sigrid Poser; Inga Zerr (Human Genetics, 2001)